Simultaneous Bilateral Knee Injection of Methylprednisolone Acetate and the Hypothalamic-Pituitary Adrenal Axis: A Single-Blind Case-Control Study. (March 2014) - Habib, George; Khazin, Fadi; Jabbour, Adel; Chernin, Mark; Badarny, Samih; Hakim, Jeries; Artul, Suheil
Objective: The objective of this study was to evaluate the effect of simultaneous bilateral intra-articular injection (IAI) of methylprednisolone acetate (MPA) on the hypothalamic-pituitary-adrenal axis in patients with knee osteoarthritis. Methods: Nonselected patients with symptomatic bilateral knee osteoarthritis had simultaneous IAI of 80 mg MPA at each knee (group 1). Just before the injection and on weeks 1, 2, 4, 6, and 8 after it, patients had 1 µg adrenocorticotropin hormone stimulation test. Age- and sex-matched patients had simultaneous IAI of 60 mg of hyaluronic acid in each knee (group 2) and the same protocol of adrenocorticotropin hormone stimulation tests. Demographic, clinical, and laboratory parameters were documented in all the patients. Secondary adrenal insufficiency (SAI) was defined as poststimulation serum cortisol levels of less than 18 µg/dL. Results: Twenty patients were enrolled in each group. There were 15 women and 5 men in each group. Mean age of the patients in group 1 was 60.3 (SD, 7.6) years. Twelve patients (60%) from group 1 had evidence of SAI versus 3 patients in group 2 ( P = 0.003). In all the patients who had SAI in group 1, it was observed in week 1 with decreasing frequency of SAI at the subsequent time points. Yet, 2 patients (10%) from group 1 had evidence of SAI 8 weeks after the IAI. Secondary adrenal insufficiency did not significantly correlate with any demographic, clinical, or laboratory parameter. Conclusions: Secondary adrenal insufficiency was very common following simultaneous bilateral IAI of 80 mg of MPA. Although it was transient, SAI could still be observed nearly 2 months after the IAI, in 10% of the patients.